Inclusive education through technology: a systematic review of types, tools and characteristics - Navas-Bonilla, Carmen del Rosario; Guerra-Arango, Julio Andrés; Oviedo-Guado, Daniel Alejandro; Murillo-Noriega, Daniel Eduardo (Frontiers in Education, 2025)
Technologies that contribute to inclusive education are digital tools and specialized devices that facilitate equitable access to learning for students with diverse abilities. Understanding these technologies allows for the personalization of teaching methods, the removal of barriers that limit participation for students with differences, and the promotion of a more accessible and equitable educational environment for all. This study aims to identify and analyze practices and technologies that foster the participation of students with diverse needs. A systematic review was conducted following PRISMA guidelines, gathering responses to the research questions from 159 studies. The Scopus database was utilized, with three blocks of keywords related to technology, inclusion, and education. The findings indicate that educational technologies transform the learning environment into a more inclusive and accessible one by adapting to the diverse needs of students. Tools such as mobile devices, interactive applications, and augmented reality help to remove barriers for students with disabilities or in various contexts, facilitating personalized and equitable learning. Additionally, these technologies promote the development of critical skills and encourage collaboration among students, enriching both their academic training and social integration. Thus, technological inclusion becomes a key factor in maximizing the potential of each student within a diverse educational system.